Assessing and comparing alternative certification programs: The teacher-classroom-community model - Dori, Yehudit Judy; Goldman, Daphne; Shwartz, Gabriella; Lavie-Alon, Nirit; Sarid, Ariel; Tal, Tali (Frontiers in Education, 2023)
Alternative certification programs (ACPs) differ from traditional teacher certification programs in their target populations, duration, tools they employ, their pedagogy, and subject matter curricula. Given the acute shortage of excellent teachers, especially in STEM, significant efforts and resources are invested in ACPs so they prepare highly qualified teachers. Yet, novice teachers face difficulties during their initial integration into the school system. To better understand the state of affairs, we investigated and compared the integration into the school system of graduates of five major Israeli ACPs that are tailored for diverse student-teacher target audiences. The study goals were to (1) investigate and compare the integration of graduates of the five ACPs into the teaching profession with respect to five teacher-related aspects: (a) self-efficacy, (b) commitment to the teaching profession, (c) challenges encountered, (d) leadership roles, and (e) teamwork; (2) identify ACP characteristics that support the graduates’ integration into the teaching profession. The teacher-classroom-community model we propose, holistically connects three aspects: affective – the teacher, the teaching profession – the classroom, and peer interaction and leadership – the school community. The model provides a common language for comparing how the different ACPs prepared their graduates toward the teaching profession. The model is instrumental for identifying ACP characteristics that support graduates’ integration into teaching and facilitating ACP evaluation by connecting several aspects of teachers’ professional lives. The findings depict a complex picture that reflects the different ACPs' characteristics targeted at diverse audiences. For example, graduates of STEM-oriented programs perceive the different kinds of knowledge, including content knowledge, pedagogical knowledge, and pedagogical content knowledge, as most important to their roles in schools. They undertake fewer roles, and the ones they do assume are discipline-related. Graduates of the more social-leadership-oriented programs identify developing leadership skills as most beneficial and they undertake more leadership-related roles. The research highlights key aspects that teacher education leaders should consider and use for self-evaluation of their ACPs. The strength of this study stems from proposing and applying the teacher-classroom-community model for evaluating teacher certification programs in several contexts and for diverse groups along with their integration into schools.